Perceptual Audio Coding Using a Time-Varying Linear Pre- and Post-Filter - Edler, Bernd; Faller, Christof; Schuller, Gerald (109th AES Convention, 2000)
Recently a new concept for perceptual audio coding was presented, which is based on a prefilter in the encoder and a corresponding postfilter in the decoder, both controlled by a psychoacoustic model. It enables individual selection of spectral and temporal resolutions for irrelevancy reduction and redundancy reduction. This paper addresses problems related to the efficient transmission of the filter parameters and presents techniques for efficient temporal and spectral modeling of masked thresholds using linear time-varying filters.: <p